Examining the perspectives of gender development and inequality: A tale of selected Asian economies - Wajid Ali; Ambiya; Devi Prasad Dash (Administrative Sciences, 2023)
The rising concern about gender inequality among the economies in South, South-East, and Eastern Asia motivates us to study the context of gender development in terms of bridging gender disparity. To show the impact, the data has been extracted from various authentic sources- Varieties of Democracy (V-Dem), World Bank Development Indicators database, Sustainable Development Index, The Observatory of Economic Complexity and Human Development Reports of the 24 South, South-East, and East Asian economies from period 2000-2020. This research was carried out empirically using various techniques such as the Ordinary Least Squared Method (OLS), Generalized Methods of Moments (GMM), and Generalised Quantile Regression. The findings of the research show a significant impact of FDI and Economic Complexity in the reduction of gender inequality. Along with this, access to justice and electoral democracy will be providing more representation to women by reducing the gender gaps. Several policy implications have been proposed following the results of the study.
Keywords: 350; Asia; democracy; foreign aid; foreign direct investment; gender inequality